The downhole behavior of the chemicals of hydraulic fracturing - an insight to the nature of biocides and surfactants underground - Kahrilas, Genevieve A., author; Borch, Thomas, advisor; Farmer, Delphine K., committee member; Henry, Charles S., committee member; Blotevogel, Jens, committee member (Colorado State University. Libraries, 2016)
In a time period and society surrounded by a surplus of information, there is currently mystery and confusion surrounding the organic chemicals added to hydraulic fracturing ("fracking") fluids. Not only is it unclear what chemicals specifically are being used in some instances, but there is little to no information existing about the transformations these chemicals may undergo once underground ("downhole") and subjected to elevated heat and pressure for the duration of a fracturing operation. Several kilometers downhole, these organic chemicals are exposed to temperatures up to 200 °C, pressures above 10 MPa, high salinities, and a pH range from 5 - 8. Despite this, very little is known about the fate of HFF additives under these extreme conditions. Chemical transformations may directly affect the toxicity of the chemicals as they emerge from the downhole environment with the rest of the "flowback" wastewater. Therefore the following chapters of this dissertation serve to classify existing information and to probe the basic effects of the downhole fracturing environment on chemical stability and transformation. Chapter 1 provides a brief introduction to and rationale for the research presented in the following pages. Some of the general purposes for chemicals within hydraulic fracturing fluids (HFFs) are discussed, as well as some of the reason for the controversy which exists today. Additionally, chapter 1 outlines the research objectives which inspired the original research presented afterwards. Chapter 2 of the dissertation servers as the first existing literature review on the biocides utilized in hydraulic fracturing. Biocides are critical components of hydraulic fracturing ("fracking") fluids used for unconventional shale gas development. Bacteria may cause bioclogging and inhibit gas extraction, produce toxic hydrogen sulfide, and induce corrosion leading to downhole equipment failure. The use of biocides has spurred a public concern and debate among regulators regarding the impact of inadvertent releases into the environment on ecosystem and human health. Chapter 2 provides a review of the potential fate and toxicity of biocides used in hydraulic fracturing operations. Physicochemical and toxicological aspects will be discussed as well as knowledge gaps that should be considered when selecting biocides: (1) uncharged species will dominate in the aqueous phase and be subject to degradation and transport whereas charged species will sorb to soils and be less bioavailable; (2) many biocides are short-lived or degradable through abiotic and biotic processes but some may transform into more toxic or persistent compounds; (3) understanding of biocides' fate under downhole conditions (high pressure, temperature, salt and organic matter concentrations) is limited; (4) several biocidal alternatives exist, but high cost, high energy demands, and/or formation of disinfection byproducts limit their use. Chapter 3 serves as the first research experiment outlining a model for testing the behavior of HFF additives downhole. Here, stainless steel reactors are used to simulate the downhole chemistry of the commonly used HFF biocide glutaraldehyde (GA). The results show that GA rapidly (t1/2 < 1 hr) autopolymerizes, forming water-soluble dimers and trimers, and eventually precipitates out at high temperatures (~140 °C) and/or alkaline pH. Interestingly, salinity was found to significantly inhibit GA transformation. Pressure and shale did not affect GA transformation and/or removal from the bulk fluid. Based on experimental second-order rate constants, this chapter provides a working kinetic model for GA downhole half-life predictions for any combination of these conditions (within the limits researched) was developed. The findings outlined in chapter 3 illustrate that the biocidal GA monomer has limited time to control microbial activity in hot and/or alkaline shales, and may return along with its aqueous transformation products to the surface via flowback water in cooler, more acidic, and saline shales. Chapter 4 builds upon the framework set by chapter 3 to analyze another chemical commonly used in HFFs: nonylphenol ethoxylates (NPEs). NPEs are commonly used as surfactants and corrosion inhibitors in hydraulic fracturing fluids. While known to biodegrade to nonylphenol (NP), a known endocrine disrupting compound, little is known about the fate and mobility of NPEs under the extremes (temperatures, pressures, and salinities) in unconventional reservoirs. Chapter 4 presents evidence of abiotic NPE degradation directly into NP by means of hydrolysis under simulated downhole conditions (100 °C, 20 bar), revealing a previously unrecognized transformation pathway. The effects of both salinity and shale interactions were also studied, indicating that salt (NaCl) drastically accelerated hydrolysis kinetics resulting in a faster and increased production of NP, while shale induced significant sorption. Sorption to colloidal shale may result in transport of the downhole-generated NP to the surface along with the flowback and produced water. The findings presented in chapter 4 suggest that hydraulic fracturing fluids may return via flowback-produced water in a form that is more toxic than what was originally injected. Chapter 5 of the dissertation presents the conclusions of the work presented here as well as future directions for research about downhole behavior of organic chemical additives to HFFs, using this body of work as a platform.
Keywords: downhole; glutaraldehyde; nonylphenol; fracking; biocides; hydraulic fracturing